KATA BERMAKNA KONOTASI DALAM NOVEL NEGERI 5 MENARA KARYA AHMAD FUADI: ANALISIS BENTUK DAN MAKNA - Irwanzi '; Charlina '; Hasnah Faizah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This reseach aims to identificate and meaning of the conotation words in the novel entitled Negeri 5 Menara by Ahmad Fuadi. This reseach used descriptive method with identification technique. The results showed there are four form of connotation word founded in the novel entitled Negeri 5 Menara by Ahmad Fuadi (1) form of root; (2) form of affix consisting of a frefix meN-, di, ber, and ter; suffix -an and -lah ; konfix di-i, ber-an, ke-an, and meN-kan; and simulfix; (3) the form of reduplication, which consists of the word intact, said the change of sound, words repeated with affix, and (4) the form of the compound is not a compound. The meaning of words contained in the novel entitled Negeri 5 Menara there are thirty-nine connote words, the meaning of the words consisting of (1) no spirit; (2) anxiety; (3) quick movement; (4) clean and beautiful; (5) noisy; (6) good, good and big ; (7) fear and scary; (8) lost; (9) dark; (10) landed; (11) swell; (12) went to evening;(13) covering and enveloping; (14) not confortable, pain, and sick; (15) shake; (16) is irradiated; (17) brighten; (18) fierce and firmly; (19) given motivation; (20) ; glance (21) angry and furious; (22) self entertaining; (23) against; (24) exit; (25) sadnes, upset, and emotion; (26) not suitable; (27) prime or beat; (28) feels; (29) many; (30) find the meaning; (31) happy; (32) hobbled; (33) sounds gusts and donts stop; (34) thief; (35) quiet or silent; (36) dizzy or sick; (37) drowsinnes; (38) light fare; and meaning (39) alone.Key Words : connotation word, connotation form, connotation meaning